2007
DOI: 10.1258/095646207781568574
|View full text |Cite
|
Sign up to set email alerts
|

HIV and related infections in a sample of recyclable waste collectors of Brazil

Abstract: Urine specimens from pregnant and non-pregnant women inhibitory to amplification of Chlamydia trachomatis nucleic acid by PCR, ligase chain reaction, and transcription-mediated amplification: identification of urinary substances associated with inhibition and removal of inhibitory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
4
2
Order By: Relevance
“…Compared with the prevalence in other Brazilian populations, the prevalence determined in this study was within the confi dence interval range recorded for patients attending an STD clinic (13%; 95% CI: 10.0-16.5) 20 , non-injection drug users (14%; 95% CI: 11.7-16.5) 21 and individuals reporting to an HIV testing and counseling center (14.6%; 95% CI: 11.2-18.0) 22 . Nevertheless, relative to other reported data on recyclable waste collectors, the prevalence found in the present study was lower than that observed in Santos, Brazil (34.4%; 95% CI: 28.5-40.2) 14,15 . This difference may refl ect differences in the rates of risky behaviors between the studied groups in Goiânia and Santos.…”
Section: Discussioncontrasting
confidence: 97%
“…Compared with the prevalence in other Brazilian populations, the prevalence determined in this study was within the confi dence interval range recorded for patients attending an STD clinic (13%; 95% CI: 10.0-16.5) 20 , non-injection drug users (14%; 95% CI: 11.7-16.5) 21 and individuals reporting to an HIV testing and counseling center (14.6%; 95% CI: 11.2-18.0) 22 . Nevertheless, relative to other reported data on recyclable waste collectors, the prevalence found in the present study was lower than that observed in Santos, Brazil (34.4%; 95% CI: 28.5-40.2) 14,15 . This difference may refl ect differences in the rates of risky behaviors between the studied groups in Goiânia and Santos.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, unprotected sex with multiple partners was associated with HCV infection according to the univariate analysis of data obtained from the study population. These sexually risky behaviours have been reported by other authors (Terrault 2002, Wang et al 2007, Alter 2011) and appear to be common in this population (Rozman et al 2007, 2008). It should be stressed that most preventative policies related to STIs are aimed at groups with higher exposure risks and do not include recyclable waste collectors.…”
supporting
confidence: 87%
“…The 1.6% prevalence rate of HCV infection found in these individuals in Goiânia was similar to that observed in a multicentric population-based study in the capital cities of Brazil (1.38%; 95% CI: 1.12-1.64) (MS/SVS 2011). Nevertheless, relative to other Brazilian recyclable waste collector populations, this prevalence was lower than the prevalence reported in Santos (12.4%) (Rozman et al 2007, 2008). This difference may reflect differences in the rates of parenteral and sexually risky behaviours between these populations in Goiânia and Santos.…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…[2] Several studies have reported the existence of work-related health and safety risks for waste collectors such as exposure to elevated concentrations of biological aerosols,[34567] respiratory and gastrointestinal complaints,[289101112] infectious diseases like hepatitis A, B, and C, HIV, and syphilis. [131415]…”
Section: Introductionmentioning
confidence: 99%